Major Pronin Stories by L. Ovalov – The Beginning of a Mythological Hero - Maja Pandžić ([sic], 2022)
The image of Major Pronin, a fictional counterintelligence operative of the All-Russian Extraordinary Commission for Fighting Counterrevolution and Sabotage has been well known throughout Russia for years. Yet, few could name his author, Lev Ovalov, and even fewer philologists have shown interest in analyzing the stories he originated from. By offering a detailed analysis of Ovalov’s first Pronin story “The Blue Swords” (“Sinie mechi”) this article aims to reveal some of the principal reasons this literary character became a cultural phenomenon. Relying on the comparative mythology theories of scholars such as Joseph Campbell and David Adams Leeming, it proposes that Pronin falls into the category of (Soviet) mythological heroes. More precisely, his traits and actions provide inspiration and guidance for the Soviet people and thus work to reinforce Soviet identity during a difficult time in history. The monomyth structure revealed in the storyline supports this theory, as do the mythological archetypes and relationships enriching the plot.